Cryptography and information security in the Balkans : second International Conference, BalkanCryptSec 2015, Koper, Slovenia, September 3-4, 2015, Revised selected papers /: second International Conference, BalkanCryptSec 2015, Koper, Slovenia, September 3-4, 2015, Revised selected papers. (2016) - Unknown
No abstract available